2020
DOI: 10.21873/anticanres.14088
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Endoglin (sCD105) as a Novel Biomarker for Detecting Aggressive Prostate Cancer

Abstract: Background/Aim: We have previously found elevated levels of endoglin (CD105) in the prostate cancer (PC) tissue of men with poor prognosis, compared to men with indolent disease. Herein, we examined whether plasma levels of the soluble form of CD105 (sCD105) differ according to the PC grade at diagnosis. Patients and Methods: We measured sCD105 in 73 subjects with biopsy-confirmed PC at the Durham, North Carolina, Veteran Affairs Health System. The association between sCD105 and intermediate/high-grade PC risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Endoglin shedding has also been shown to suppress tumor angiogenesis. Indeed, low soluble endoglin is associated with aggressive prostate cancer, whereas elevated soluble endoglin is associated with recurrence‐free survival in patients 100,101 …”
Section: Tgf‐β Superfamily Co‐receptors and Their Role In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Endoglin shedding has also been shown to suppress tumor angiogenesis. Indeed, low soluble endoglin is associated with aggressive prostate cancer, whereas elevated soluble endoglin is associated with recurrence‐free survival in patients 100,101 …”
Section: Tgf‐β Superfamily Co‐receptors and Their Role In Cancermentioning
confidence: 99%
“…Indeed, low soluble endoglin is associated with aggressive prostate cancer, whereas elevated soluble endoglin is associated with recurrence-free survival in patients. 100,101 While endoglin is primarily expressed in the tumor vasculature, recent studies have identified a role for endoglin in cancer cells and other tumor-associated cell types. 102 For example, when expressed in cancer cells, endoglin is associated with cancer progression in endometrial cancer, ovarian cancer, hepatocellular carcinoma, Ewing sarcoma, and melanoma.…”
Section: Cancermentioning
confidence: 99%
“…Similar to THY1, ENG + ASPN + fibroblasts were also elevated in cribriform prostate cancer. Both ENG and ASPN are associated with adverse outcomes and may promote the progression of aggressive prostate cancer [32,[49][50][51]. While the overall expression of NT5E, TNC, and PDGFRβ did not change in the tumor microenvironment, ASPN expression was altered in these cells.…”
mentioning
confidence: 95%
“…Similar to FAP, Thy-1 cell surface antigen (THY1) is also overexpressed in prostate CAFs [47], and it may have a role in regulating cancer stem cells [48]. Endoglin (ENG) is another CAF marker associated with adverse outcomes, and it has been shown to promote castration-resistant prostate cancer [49][50][51]. Tenascin C (TNC), 5'-nucleotidase ecto (NT5E), and platelet-derived growth factor receptor beta (PDGFRβ) are other CAF markers that are currently candidate targets for imaging or therapeutics [52][53][54][55].…”
mentioning
confidence: 99%
“…is involved in TGF-β1 induced cell signal transduction (1,(32)(33)(34)(35). Although, the intracellular mechanisms by which and how CD105 modulates TGF-β1 signalling have been extensively studied, they need further clarification (7,9,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
mentioning
confidence: 99%